2022
DOI: 10.1353/ecs.2022.0060
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of Eighteenth Century Collections Online (ECCO)

Abstract: His research team focuses on the theory and methods in the analysis of complex natural and social systems. He thanks the Academy of Finland for funding this research (Grant 348946).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…By examining all of these different features and their distributions across historical texts, register analysis can help us better understand the ways in which language is used to construct historical narratives. Many of the features of dimensions 1 and 5 are demonstrated (highlighted with bolding and italics, respectively) in the following passage from a text in the "history" genre: 4 He summoned a Parliament, to whom he made bitter complaints against the irruption of the Scotch, the absurd imposture which was countenanced by that nation, the cruel devastation which they had spread over the northern counties, and the complicated affront which had thus been offered both to the King and kingdom of England. (David Hume, 1759, The history of England)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By examining all of these different features and their distributions across historical texts, register analysis can help us better understand the ways in which language is used to construct historical narratives. Many of the features of dimensions 1 and 5 are demonstrated (highlighted with bolding and italics, respectively) in the following passage from a text in the "history" genre: 4 He summoned a Parliament, to whom he made bitter complaints against the irruption of the Scotch, the absurd imposture which was countenanced by that nation, the cruel devastation which they had spread over the northern counties, and the complicated affront which had thus been offered both to the King and kingdom of England. (David Hume, 1759, The history of England)…”
Section: Discussionmentioning
confidence: 99%
“…ECCO contains over 30 million pages of text, from over 200,000 documents, making it much larger than most hand-curated historical corpora. [3] In 2004 Gale claimed that ECCO contained every significant work in the English langugage printed in the eighteenth century, plus thousands of other important works [3, p. 56], though studies have shown that its representation of the entirety of the eighteenth century publishing landscape is uneven [4]. Nevertheless, a linguistic analysis which could confidently be applied to this dataset would provide new opportunities to study the wide variety of texts within ECCO, including pamphlets, legal documents and statutes, technical texts or instruction manuals, and non-elite writing.…”
Section: Introductionmentioning
confidence: 99%
“…Gerlach 2020). Eighteenth Century Collections Online (ECCO) is a collection of English texts from 1701-1800 containing around 184,386 publications, which is around 54% of the titles listed in a bibliography of the era (Tolonen et al 2022). The digitization project HathiTrust contains more than 17 million digitized publications where text mining is permitted, allowing a corpus of 210,266 fiction texts to be created (Underwood et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These text collections are not balanced -the representativeness of these contents for any research question is in itself an open research issue (see e.g. Tolonen et al 2022) -which leaves the selection of relevant works up to the researcher. By contrast, while traditional linguistic corpora have been specifically designed to be balanced, there is increasingly discussion of using more complex collections for linguistic or historical study by a more thorough understanding of the representativity of each collection used (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a modified version of BLAST (Vesanto, 2019)-a bioinformatics algorithm for finding regions of similar sequences, first experimented with Finnish newspapers (Salmi et al, 2020)-was shown to be an OCR error-resilient way of detecting textual overlaps. As part of the High-Performance Computing and Historical Discourses (HPC-HD) project, this technique was applied to EEBO-TCP and ECCO, namely, corpora of books printed in Britain between 1450-1800 (Tolonen et al, 2022;Lahti et al, 2019).…”
mentioning
confidence: 99%